August Ludwig von Rochau and Realpolitik as historical political theory. Issue 3 (2nd September 2018) - Kelly, Duncan
ABSTRACT: Neither self-styled radical 'realists' who reject the sort of liberalism inspired by John Rawls, nor liberal 'realists' who reject other forms of apparently utopian politics, properly take the measure of how far their accounts of realism recall the historical political theory of nineteenth-century European Realpolitik . This article sketches the evolution of that style of political theory in the thought of its conceptual pioneer, August Ludwig von Rochau, and outlines the bases of his understanding of state power. Reconstructing his argument not only suggests an alternative genealogy for modern realism in political theory, but it also offers a challenge. For behind Rochau's Realpolitik lies a strong judgment about how ideas are politically consequential only when aligned with state power under modernity, and that such alignments are both historically conditioned and difficult to judge. Rochau's challenge for realism in contemporary liberal political theory implies that its general antipathy towards writing about the historical evolution of the state and its structural power threatens to leave it as unmoored from practical politics as the so-called ideal-theorists that realists so often profess to criticize.